SAOMI (SAOENG MIMPI): EDUKASI CERDAS MEMBANGKITKAN JUTAAN PELANGI - Styawan, Bayu; Saputra, Venza Rhoma; Miratunnisa, Ima; Alamsyah, Indra; Sulardi, Anom (Program Kreativitas Mahasiswa - Pengabdian Kepada Masyarakat, 2013)
Statistical Data from the Ministry showed that Social abandoned children in Indonesia reached 4.8 million children. Most of them are accommodated in orphanage. But the orphanage they lived is still much less fulfilled facilities, so that they tend to get bored with the activities in the orphanages. It needs other activities that could eliminate their bored feeling. One of the methods is smart education activity such as an introduction to the profession, self-employment training, and write training. After smart education activities implemented at the orphanage, it will open their mindset and will increase their independence.